Hubungan Motivasi Belajar dengan Hasil Pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA) pada Mahasiswa Semester 7 Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Muhammadiyah Tangerang - Agus Sulaeman; Winda Dwihudhana (LP4MK STKIP PGRI Lubuklinggau, 2019)
This study aims to determine the relationship between learning motivation towards the learning achievement of Indonesian language for non native speakers (BIPA) at 7th semester students in Indonesian Language and Literature Study Program. The research methods used was quantitative method with correlation design. The instruments of research were interviews, observation and questionnaire respondents' statements to 40 students at 7th semester. This was done in order to find out how the relationship between learning motivation and learning achievement by using correlational, determination and significance test. The purpose was to improve and evaluate the learning achievement. Due to the results of the calculation analysis by using Pearson correlation coefficient formula, there was a positive effect of correlation between learning motivation towards the learning achievement, which was equal of r = 0.50 that includes a fairly strong category (0.40–0.599). The results of testing the formula of t count is > t table that is 0.62 > 0.31, which means that H0 was rejected and H1 was accepted. It means, the learning motivation as variable X has a significant influence on the learning achievement as variable Y. So, BIPA teaching materials are appropriate to be designed.